2015
DOI: 10.1371/journal.pone.0132500
|View full text |Cite
|
Sign up to set email alerts
|

The THERMOSENSITIVE MALE STERILE 1 Interacts with the BiPs via DnaJ Domain and Stimulates Their ATPase Enzyme Activities in Arabidopsis

Abstract: The Arabidopsis TMS1 encodes a heat shock protein identical to the Hsp40 protein AtERdj3A and plays important roles in the thermotolerance of pollen tubes and other plant tissues. Despite its importance to plant growth and reproduction, little has been known about its mechanisms underlying thermotolerance of plants. In this study, the relationship between TMS1 and the Hsp70 proteins, Binding Immunoglobulin Proteins (BiPs) was explored to understand the molecular mechanisms of TMS1 in thermotolerance of plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Genes that are co-expressed with the candidate genes are also involved in abiotic stress response, such as HIPP26 gene, involved in Cd detoxification in plants, while the SRX gene participates in the signaling mechanism in response to photooxidative stress (Rey 2007 andTehseen 2010). Furthermore, there are several genes identified in this study, or co-expressed with them, that are involved in thermotolerance, such as DJC65, TMS1, DNAJ, and TMS1 (Chiu 2013, Ma 2015and Suzuki 2008. In our study, we also found a potential PGPB interaction gene, ERF9, which is an ethylene response factor that negatively regulates plant defense (Huang 2016).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Genes that are co-expressed with the candidate genes are also involved in abiotic stress response, such as HIPP26 gene, involved in Cd detoxification in plants, while the SRX gene participates in the signaling mechanism in response to photooxidative stress (Rey 2007 andTehseen 2010). Furthermore, there are several genes identified in this study, or co-expressed with them, that are involved in thermotolerance, such as DJC65, TMS1, DNAJ, and TMS1 (Chiu 2013, Ma 2015and Suzuki 2008. In our study, we also found a potential PGPB interaction gene, ERF9, which is an ethylene response factor that negatively regulates plant defense (Huang 2016).…”
Section: Discussionmentioning
confidence: 70%
“…Mutation in this gene affects the secretion of proteins and lipids, culminating in a visibly altered pollen surface (Iwata 2012). TIN1 is co-expressed with TMS1 (thermosensitive male sterile 1), a gene involved in thermotolerance in pollen tubes and response to heat shock treatment in seedlings (Ma 2015); BF1C, a regulator of thermotolerance, which encodes a protein that accumulates rapidly and is localized in the nuclei during heat stress (Suzuki 2008); and DNAJ, which encodes a chaperone belonging to heat shock protein family involved in response to various environmental stresses.…”
Section: Selection Of Candidate Genes Responsible For Plant Growth Prmentioning
confidence: 99%
“…Heat stress affects the tapetum layer of pollen and reduces the nutrition supply, especially during microspore development. This shortage of nutrient supply affects the male gametogenesis, and hamper the formation of microspore cells and ultimately causes pod abortion (Ma et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…J domain proteins (Hsp40) found in the ER lumen bind BiP proteins and stabilize their interactions with client unfolded proteins (Misselwitz et al, 1998;Yamamoto et al, 2008). ERdj3A, which is induced under ER stress, contains a Cterminal protein disulfide isomerase domain that has reductive capabilities on substrates in vitro (Yang et al, 2009), in addition to a HSP40 ATPase activity (Ma et al, 2015). This suggests that ERdj3A may act on a specific subset of client proteins.…”
Section: Send In the Cavalry: Downstream Effectors During Er Stressmentioning
confidence: 99%